Exploring Factors that Contribute to Regular Participation and Practice in Cognitive Stimulation Training for Mild Cognitive Impairment: A Qualitative Study - Srisuwan, Patsri; Nakawiro, Daochompu; Chansirikarnjana, Sirinthorn (Journal of Aging Research And Healthcare, 2017)
Background and Objective: Cognitive stimulation training was effective in reducing risk of cognitive decline and dementia in patients with mild cognitive impairment. The present study aimed to explore factors that contribute to regular participation and practice cognitive stimulation training for elderly patients with mild cognitive impairment. Materials and Methods: Data were collected through individual face-to-face interviews with 25 elderly subjects with mild cognitive impairment, and analyzed using interpretive description method. Results: Five core themes emerged from the analysis of data: (i) program with four subthemes of “interesting session, ” “effective teaching materials,” “suitable duration and frequency” and “small group activities;” (ii) group facilitators with three subthemes of “good explanation,” “always facilitate” and “friendly personality;” (iii) homework assignments with two subthemes of “suitable content” and “can adapt in daily living;” (iv) family members with two subthemes of “supporting” and “sharing;” (v) before and after class notification. Conclusion: Increasing awareness of holistic factors including in clinic and at home should be emphasized in planning cognitive stimulation training. Having an effective program and facilitators and collaboration from family member were the keys of successful training.
Keywords: cognitive stimulation training; mild cognitive impairment; elderly; participation; qualitative study.